2012
DOI: 10.1074/jbc.m112.360628
|View full text |Cite
|
Sign up to set email alerts
|

Small Efficient Cell-penetrating Peptides Derived from Scorpion Toxin Maurocalcine

Abstract: Background: This study aimed at developing a new set of maurocalcine-derived cell-penetrating peptides from truncation. Results: Several truncated peptides were designed and evaluated for Cy5 dye cell penetration. Conclusion: All truncated peptides are competitive cell-penetrating peptides, many of them comparing favorably well with TAT. Significance: Maurocalcine-derived truncated cell-penetrating peptides differ in their properties, enlarging the potential fields of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
3
30
1
Order By: Relevance
“…In contrast, our findings herein demonstrated that TAT is unnecessary for NoxA1ds to cross cell membranes, and we attribute this in part to the positively charged lysines in the C terminus of NoxA1ds and the alternating hydrophobic/hydrophilic amino acid structure of NoxA1ds. Indeed, other short peptides with similar hydropathy patterns have proven highly cell permeant and thus support our findings (50).…”
Section: Epvd(y3 A)-lgkakv 205supporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, our findings herein demonstrated that TAT is unnecessary for NoxA1ds to cross cell membranes, and we attribute this in part to the positively charged lysines in the C terminus of NoxA1ds and the alternating hydrophobic/hydrophilic amino acid structure of NoxA1ds. Indeed, other short peptides with similar hydropathy patterns have proven highly cell permeant and thus support our findings (50).…”
Section: Epvd(y3 A)-lgkakv 205supporting
confidence: 88%
“…Notwithstanding the broadly demonstrated effectiveness of related peptides by parenteral, peritoneal, subcutaneous, and direct application to blood vessels using gene therapy (46,50), the limitations in the use of peptides as "druggable" therapeutics are obvious. These include a very limited oral bioavailability due to peptide degradation in the gut.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…The chemical synthesis of Tyr-L-MCa and the folding / oxidation process were not affected by the extra tyrosine residue added to the N-terminal end of the peptide. These results together with previous observations of the Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/1/15 1:15 PM great tolerance in sequence variation with respect to the cell penetrating properties of MCa [28,29] strongly suggest that Tyr-L-MCa should retain its native properties. The position of the extra tyrosine residue ensures that iodination occurs in a convenient way, without accessibility problems and modification of the native sequence.…”
Section: Discussionsupporting
confidence: 76%
“…35 Hence, the reason for the lack of internalization of the peptide in our studies, especially in the cancer cells, is not clear. Maurocalcine is a highly potent CPP.…”
Section: Cpp-dy676 Conjugates Into Cancer and Noncancer Cellsmentioning
confidence: 71%